2010
DOI: 10.1007/s10765-010-0900-z
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Technique for Experimental Thermophysical Characterization of Phase-Change Materials

Abstract: The major objective of this project is to use phase-change materials (PCMs) as integrated components in passive solar heat recovery systems. The suggested approach involves experimental investigations and characterization of the global behavior of a parallelepiped "material wrap" filled with the PCM. The experimental apparatus permits simultaneous measurements of heat fluxes and temperatures. It also allows imposing and measuring temperatures variations with respect to selected time scales between the two pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…5). An imposed temperature change on each face of the sample is set and simultaneous measurements of the temperature and exchanged heat flux variations during heating and cooling processes allow the determination of the thermo-physical properties of the sample, namely the thermal conductivity λ and the specific heat capacity cp (Younsi et al 2011). The heat flux and the temperature on both sides of the sample are measured simultaneously.…”
Section: Experimental Setup and Samplesmentioning
confidence: 99%
“…5). An imposed temperature change on each face of the sample is set and simultaneous measurements of the temperature and exchanged heat flux variations during heating and cooling processes allow the determination of the thermo-physical properties of the sample, namely the thermal conductivity λ and the specific heat capacity cp (Younsi et al 2011). The heat flux and the temperature on both sides of the sample are measured simultaneously.…”
Section: Experimental Setup and Samplesmentioning
confidence: 99%
“…6(b) presents the temporal variation of total (sensible and latent) and latent energy stored in the system during charge and discharge processes for various capsule radii. The total energy stored in the system is calculated using Equation (10). At a given time, the total energy stored in the tank varies according to the particle size.…”
Section: Effect Of Capsule Sizementioning
confidence: 99%
“…Hence, several authors have been focused on the use of phase change materials for thermal energy storage. Experimental and numerical studies have been conducted to characterize the PCMs [10,11]. Various studies on the latent heat storage in packed beds have been found in the literature [12e14].…”
Section: Introductionmentioning
confidence: 99%
“…Vivekanandan et al [10] conducted analysis of using ANSYS on temperature distribution. Younsi et al [11] manufactured a rectangular at the boundaries of the material in the direction of the fluxes. He highlights the influence of supercooling on the release and rate of release of the heat.…”
Section: Literature Reviewmentioning
confidence: 99%